Can technical Analysis Indicators Predict Future Stock Prices? Evidence from Elliot Wave and Fibonacci Retracement - Fillah Dwi Ardiansyah; Choirul Nikmah; Muhammad Haziq Bin Azri Irwandy (Jurnal Ilmiah Manajemen Kesatuan, 2025)
Investors often find it challenging to track stock price fluctuations, especially when making decisions about buying and selling stocks. This study confirms and validates the Elliott wave scenario in analyzing the patterns of future stock price movements for PT Bank Central Asia Tbk and PT Bank Rakyat Indonesia Tbk. The primary focus is on the effectiveness of technical analysis in measuring medium-term price changes from 2020 to 2025, utilizing the Elliott wave oscillator and Fibonacci retracement tools. The findings indicate that BBCA's stock price in 2025 is likely to undergo a correction pattern, with a potential support area at the 50.00% retracement level of IDR 7,600. Meanwhile, BBRI's stock price movement in 2025 is expected to exhibit a bearish trend, with a support area at the 61.80% retracement level of IDR 3,770. Looking ahead, further research into stock price forecasting techniques would significantly contribute to the existing literature and provide valuable insights for investors and traders in predicting stock price movements.